Analysis of Utilization of Learning Management System (LMS) as an Effort to Optimize Governance of Village-Owned Enterprises (BUMDES) in Bojonegoro Regency - Musthofa, Tatag Fajrin; Rejekiningsih, Triana; Sukmawati, Fatma (Universitas Sebelas Maret, 2023)
Learning Management System (LMS) is a learning management system that documents educational material and work skills using multimedia packaging (text, animation, video, and sound) as input and content for developing student competencies. In addition to learning in the field of education, LMS can also be used as a training medium for village-owned enterprises (BUMDes). This study aims to determine the development of a proper learning management system (LMS) media for the governance learning process at (BUMDes) in Bojonegoro Regency. The method used in this research is qualitative. Based on DPMD data, out of 419 villages in Bojonegoro Regency, 393 villages already have BUMDes and are legal entities. In implementing the Learning Management System (LMS) at BUMDes, at least 6 applications have been used, namely, Village I n f o r m a t i o n S y s t e m s ( S I D ) , V i l l a g e we b s i t e s wi t h d o m a i n s , V i l l a g e F i n a n c i a l S y s t e m s (SISKEUDES), Digital Mapping, Letter C Applications and e-Commerce Applications .